X-ray tomography data of columnar joints in starch - Goehring, Lucas; Morris, Stephen W (PANGAEA, 2020)
Columnar jointing is best-known from formations in cooled lava, such as the Giant's Causeway, Devil's Postpile, or Fingal's Cave. However, these crack patterns also arise in other systems, most notably in dried starch. The data published here underlies research into the dynamical ordering of columnar joints, and the process by which they select their size or scale (Goehring and Morris, 2005; Goehring, Morris and Lin, 2006). The data set consists of nine X-ray tomographs of columnar joints in dried starch, presented as both the raw instrument data and as series of reconstructed cross-sectional images throughout the volume of the samples. There is a mixture of samples where the drying rate was monitored but not controlled, which results in columns that grow in size with depth, and samples where the drying rate of the starch was controlled by a feedback technique, which results in columns of constant size. A summary spreadsheet gives metadata associated with each sample, including the instrument settings during data acquisition. This data and the methods of its acquisition will be further detailed in an accompanying data publication, which will also include details of 3D reconstructions of columnar joints in various geophysical settings in the UK and Japan.
Keywords: columnar jointing; Columnar joints; cracks; fracture; tomography